Environmental performance of second-life lithium-ion batteries repurposed from electric vehicles for household storage systems - Spindlegger, Anna; Slotyuk, Lyubov; Jandric, Aleksander; De Souza, Ricardo Gabbay [UNESP]; Prenner, Stefanie; Part, Florian (Elsevier, 2025)
Repurposing lithium-ion batteries has proven to be a promising solution to address the rising number of end-of-life batteries that can be used for second-life energy storage systems and thus extend their service life. While previous research has provided valuable insights into the environmental benefits of battery repurposing, there is still a need to examine the repurposing process more thoroughly, in order to make well-informed decisions on the implementation of second-life battery storage systems. Therefore, this study examines the influence of different repurposing strategies on the environmental performance of second-life battery energy storage systems. A life cycle assessment was conducted, analysing four repurposing cases relating to the exchange of components, namely i) new battery management system and module casing (Base case), ii) new battery management system and reuse of module casing (Case 1), iii) new module casing and reuse of battery management system (Case 2) and iv) reuse of module casing and battery management system (Case 3). These impacts were compared to a storage system with new batteries, to determine the potential environmental benefits and identify the most suitable repurposing strategy. Our findings demonstrate significant environmental benefits of second-life battery energy storage systems across various impact categories and repurposing cases. The Base case and Case 1 resulted in environmental benefits across all impact categories. The highest benefits were observed for metal depletion with savings of 58 % and 61 %, respectively. Increased savings were obtained for Case 2 and Case 3. However, environmental drawbacks were identified for freshwater and marine ecotoxicity. In particular, Case 2 resulted in the highest drawbacks of −22 % and −16 %, respectively. These can be attributed to the allocation procedure, particularly affecting the recycling credits of battery management system recycling. The full allocation of end-of-life impacts and consequently the recycling credits to the second-life battery has not only led to a substantial increase in overall savings, but also resulted in impact categories that originally had disadvantages becoming those with the highest environmental savings. This study demonstrates the importance of carefully selecting repurposing strategies for second-life energy storage systems to maximize their environmental benefits and avoid drawbacks. Additionally, the results highlight the substantial influence of allocation procedures on overall environmental impacts, underscoring the need for clearer methodological guidance on addressing the multifunctionality of repurposed batteries.
Keywords: Battery energy storage system; Circular economy; Life cycle assessment; Lithium-ion battery; Repurposing; Second-life battery